Tau accumulates in Crohn's disease gut. Issue 7 (21st May 2020) - Prigent, Alice; Chapelet, Guillaume; De Guilhem de Lataillade, Adrien; Oullier, Thibauld; Durieu, Emilie; Bourreille, Arnaud; Duchalais, Emilie; Hardonnière, Kévin; Neunlist, Michel; Noble, Wendy; Kerdine‐Römer, Saadia; Derkinderen, Pascal; et al.
Abstract: A sizeable body of evidence has recently emerged to suggest that gastrointestinal (GI) inflammation might be involved in the development of Parkinson's disease (PD). There is now strong epidemiological and genetical evidence linking PD to inflammatory bowel diseases and we recently demonstrated that the neuronal protein alpha‐synuclein, which is critically involved in PD pathophysiology, is upregulated in inflamed segments of Crohn's colon. The microtubule associated protein tau is another neuronal protein critically involved in neurodegenerative disorders but, in contrast to alpha‐synuclein, no data are available about its expression and phosphorylation patterns in inflammatory bowel diseases. Here, we examined the expression levels of tau isoforms, their phosphorylation profile and truncation in colon biopsy specimens from 16 Crohn's disease (CD) and 6 ulcerative colitis (UC) patients and compared them to samples from 16 controls. Additional experiments were performed in full thickness segments of colon of five CD and five control subjects, in primary cultures of rat enteric neurons and in nuclear factor erythroid 2‐related factor (Nrf2) knockout mice. Our results show the upregulation of two main human tau isoforms in the enteric nervous system (ENS) in CD but not in UC. This upregulation was not transcriptionally regulated but instead likely resulted from a decrease in protein clearance via an Nrf2 pathway. Our findings, which provide the first detailed characterization of tau in CD, suggest that the key proteins involved in neurodegenerative disorders such as alpha‐synuclein and tau, might also play a role in CD.